Pengaruh Pendidikan Keluarga dan Sekolah Terhadap Pembentukan Karakter Siswa di Sekolah MA-YI Rajamandala Dan SMKN 1 Cipatat - Reza Imam Purwa Gumelar (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
The purpose of this study was to determine the effect of family and school education on the character formation of students at MA-YI Rajamandala and SMKN 1 Cipatat. This research is a quantitative research with descriptive method that focuses on family education, school and student character. The data collection technique uses a questionnaire/questionnaire, documentation. While the data analysis used descriptive quantitative analysis and inferential. The results of the study at MA-YI Rajamandala showed that there was an influence of family and school education of 13.2% with a sig value of 0.021 < 0.05 and Fcount 4.171 > Ftable 3.16. Meanwhile, at SMKN 1 Cipatat, the effect was 18.6 with a sig value of 0.000 <0.05 and Fcount 9.466 > Ftable 3.10.